2016
DOI: 10.1177/1545968316632059
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Physical Activity Intervention for Adults With Brain Impairment

Abstract: The 12-week intervention effectively increased adoption of PA in a sample of community-dwelling adults with BI immediately after the intervention but not at follow-up. Future studies should explore strategies to foster maintenance of PA participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 47 publications
(59 reference statements)
0
21
0
Order By: Relevance
“…Fourteen studies measured changes in step count using a variety of devices . Activity counts were assessed in three studies using the ActiGraph (Actigraph Corp, Pensacola), Sensewear Armband (Body Media, San Francisco), or GENEActiv (ActivInsights, Cambridge) . These devices sample activity counts associated with the user's rate of acceleration, and established cut‐points determine time spent in varying intensities of physical activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen studies measured changes in step count using a variety of devices . Activity counts were assessed in three studies using the ActiGraph (Actigraph Corp, Pensacola), Sensewear Armband (Body Media, San Francisco), or GENEActiv (ActivInsights, Cambridge) . These devices sample activity counts associated with the user's rate of acceleration, and established cut‐points determine time spent in varying intensities of physical activity.…”
Section: Resultsmentioning
confidence: 99%
“…One study reported the group by time interaction effect as partial η 2 . The other study reported between‐group effects as Cohen's d . We calculated Cohen's d effect sizes for 23 studies in which the outcomes of interest were continuous.…”
Section: Resultsmentioning
confidence: 99%
“…26,36 Tailored counseling combined with remote data-driven supervision have been critical components to increase practice and exercise. 1948 Of course, this overall motor and behavioral training strategy must be compared to conventional post rehabilitation care in randomized clinical trials for the goals of optimizing long-term activity and participation, skills practice, strengthening and conditioning.…”
Section: Mobile Health and Tele-rehabilitation Strategiesmentioning
confidence: 99%
“…This paper describes a community-based tailored program for the promotion of physical activity participation in adults with BI. The program has been shown to be effective at promoting physical activity adoption in adults with BI (Clanchy et al, 2016). The distinguishing features of the APAP in comparison to previously evaluated programs include a comprehensive pre-participation assessment mapped against the domains of the ICF in order to tailor the program to the individuals health, personal and environmental considerations; the use of a community-based rehabilitation model in preference to delivery in a fixed facility; and the inclusion of tailored behaviour change strategies in addition to structured exercise prescription and lifestyle physical activity participation.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent controlled clinical trial (Clanchy et al, 2016), stage of change was assessed using the Marcus and Simkin's (1993) staging algorithm, which classifies individuals into one of five Stages of Change on the basis of their current physical activity participation and their motivational readiness for change: Stage of Change 1 -currently does not participate in physical activity, and does not intend to start within the next 6 months; Stage of Change 2 -currently does not participate in physical activity, but are intending to start within the next 6 months; Stage of Change 3 -currently physically active but not regularly (i.e., three or more times per week for 20 minutes or longer); Stage of Change 4 -completing regular physical activity, however, have not maintained this activity level for 6 months; or Stage of Change 5 -completing regular physical activity and have maintained this activity level for 6 months or more. The assessment of stage of change for this intervention allows the practitioner to (1) determine whether the individual self-reports being insufficiently active for good health; and (2) tailor the program strategies to the participants motivational readiness for change (Blissmer & McAuley, 2002).…”
Section: Step 1 Part B: Stage Of Change Assessmentmentioning
confidence: 99%